The relation between FT3 and long-term fatigue in patients with COVID-19 - Dong, Shuo; Ding, FanRui; Wang, Yuan; Liu, Shuo; Bai, Ran; Liu, YuanYuan; Zhao, Yin; Zhu, YueRan; Liu, MengXue; Liu, Yuenan; Xing, Qian (Frontiers in Endocrinology, 2024)
Background: Under the current pandemic of Corona Virus Disease 2019 (COVID-19), The relationship between fatigue and COVID-19 has been found. Infection with COVID-19 is associated with fatigue long after the acute phase of COVID-19. Understanding the association of thyroid hormones levels with post-COVID condition, such as fatigue, is necessary to improve quality of life. Methods: This population-based cohort study was conducted in Dalian, China, from December 2022, to March 2023, using a Yidu Core platform in the First Affiliated Hospital of Dalian Medical University, that integrates medical records, laboratory tests, and all diagnosis and treatment information based on patients in hospital. Eligible individuals were 40 patients with COVID-19, Divided them into fatigue group and nonfatigue group following up by telephone using the FS-14 scale after 6 months. Analysis was conducted April 14, 2023, to April 28, 2023. The primary outcomes were the diagnoses of fatigue. The association between thyroid hormones levels and post-COVID condition, such as fatigue, was assessed using logistic regression analysis.Results: Compared with the non-fatigue group, the FT3 level in fatigue group was lower (p<0.05). FT3 was negatively correlated with fatigue after 6 months (OR 0.257, p<0.05).After adjusting for confounding factors such as age and gender, low FT3 was a risk factor for fatigue in patients with (OR 0.225, p<0.05). And the FT3 is less than 2.47 mol / L, it is the best critical value for predicting long-term fatigue, with a sensitivity of 92.3% and a specificity of 48.1%.: Most people still have fatigue 6 months after COVID-19 infection. FT3 serves as the important index to predict fatigue in patients with COVID-19. it should be closely monitored during infection.